2006
DOI: 10.1093/molehr/gal052
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of fetal DNA in maternal serum during the first trimester of pregnancy by the use of a DAZ repetitive probe

Abstract: Cell-free fetal DNA in maternal plasma or serum is at present widely investigated as a source of fetal genetic material, both in studies of pregnancy-related disorders and in planning strategies for non-invasive prenatal diagnosis. Despite the number of trials already performed on the quantitation of fetal DNA, data about the amount of DNA at the beginning of pregnancy, in particular in the first trimester, remain limited. A new probe mapping on the deleted in azoospermia (DAZ) repetitive region of the Yq chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 27 publications
1
26
0
2
Order By: Relevance
“…In this way, the primer pair used for the DAZ assay produces five amplicons with 100% identity, mapping on the 2.4-Kb repetitive motifs of the DAZ gene region (one for each of DAZ1, DAZ2, and DAZ3 and two for DAZ4). 25 Thus, the utilization of this sequence as confirmation could give a higher sensitivity compared with the SRY assay when a negative result for this gene is obtained. Likewise, a positive result for SRY in combination with negative or inconclusive results for multicopy sequences, as a result of their better sensitivity, 26 was considered a technical failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, the primer pair used for the DAZ assay produces five amplicons with 100% identity, mapping on the 2.4-Kb repetitive motifs of the DAZ gene region (one for each of DAZ1, DAZ2, and DAZ3 and two for DAZ4). 25 Thus, the utilization of this sequence as confirmation could give a higher sensitivity compared with the SRY assay when a negative result for this gene is obtained. Likewise, a positive result for SRY in combination with negative or inconclusive results for multicopy sequences, as a result of their better sensitivity, 26 was considered a technical failure.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] However, other simple and sensitive tests for fetal gender determination using a unique multicopy region of the Y chromosome, such as the DAZ family, have been developed. 16,17 Although results are encouraging, the diagnostic accuracy varies widely depending on the protocols and methods used, with sensitivity and specificity ranging from 31% to 100%. 18,19 Moreover, most data have been obtained in a research setting rather than from clinical practice.…”
mentioning
confidence: 99%
“…56: [639][640][641][642] 2010) he discovery of fetal DNA (fDNA) in maternal circulation [1] and transcervical cells has led to noninvasive prenatal genetic diagnosis and sex prediction for fetuses during early pregnancy in women [2]. Although it was recently demonstrated that fDNA in women and rhesus monkeys could be used as a tool for fetal sex determination as early as at the 5th gestational week using the Y chromosome DNA sequence as a probe for screening male fetuses with an accuracy rate of 100% [3][4][5][6], little is known about fDNA in domestic animals. In 1996, Kadokawa et al believed, based on their previous research, that fetal cells were very rare or may be absent in bovine maternal blood and that they could not be used for prenatal sexing by a PCR method [7].…”
mentioning
confidence: 99%
“…ccff DNA isolated from plasma samples from pregnant women is still a scarce resource. Results of published studies indicate that the mean number of DNA molecules found in 1 mL of plasma is around 2000, with a fetal component of around 15% ( 27,29,31 ). Both of these values are subject to a large spread across individuals, and therefore it is desirable to minimize the DNA consumption of an assay that controls for the presence of fetal DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Quantification that uses competitive PCR and MALDI-TOF MS relies on the relative evaluation of a target signal against a reference signal. Various published reports have indicated that the total amount of circulating cell-free DNA is around 2000 copies/mL of plasma and the fraction of fetal DNA is between 3% and 20% (27)(28)(29). Consequently we chose 3000 copies of single-stranded competitor DNA for the estimation of total DNA and 300 copies of competitor DNA for the estimation of fetal DNA.…”
Section: Model System and Verification Of Dynamic Rangementioning
confidence: 99%